Scaredy-cat, Splat! - Scotton, Rob. (New York : Harper, 2010)
Splat the cat accidently succeeds in being the scariest cat in the class for Halloween.
Keywords: Cats -- Easy picture; Halloween -- Easy picture; Costume -- Easy picture